Comments on Methods to Suppress Endogenous β-Galactosidase Activity in Mouse Tissues Expressing the LacZ Reporter Gene. (October 2016) - Merkwitz, Claudia; Blaschuk, Orest; Schulz, Angela; Ricken, Albert Markus
The Escherichia coli LacZ gene (encoding β-galactosidase) is a widely used reporter for gene regulation analysis in transgenic mice. Determination of β-galactosidase activity is classically performed using 5-bromo-4-chloro-3-indolyl-β-d-galactopyranoside/ferri-/ferrocyanide (X-Gal/FeCN) histochemistry. Uncertainty about the origin of the β-galactosidase signal is encountered in tissues containing high levels of endogenous β-galactosidase. Here, we show that reliable results can nevertheless be obtained in these tissues by performing the histochemical reaction under slightly basic pH conditions (pH 8–9). We further demonstrate that in this context, analysis of tissue sections may be advantageous over that of conventional whole-mount tissues because poor dye penetration and remaining tissue acidity are avoided in tissue sections. We also recommend that bacterial debris should always be carefully removed from the luminal surface of gastrointestinal tract specimens unless staining of resident microflora is deliberately used as an internal positive control in the assay. Finally, we show that 6-chloro-3-indolyl-β-d -galactopyranoside with nitrotetrazolium blue chloride works well as an alternative chromogenic substrate for visualizing LacZ reporter gene expression in cryostat sections. Its use in high endogenous β-galactosidase-expressing organs is superior over the use of X-Gal/FeCN at slightly basic pH conditions.